2021
DOI: 10.48550/arxiv.2110.11145
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Interactions of the doubly charmed state $T_{cc} ^+$ with a hadronic medium

L. M. Abreu,
F. S. Navarra,
M. Nielsen
et al.

Abstract: The recently observed doubly charmed state T + cc belongs to the family of the multiquark states called exotic hadrons. One of main goals of modern hadron physics is to determine the strucutre of these exotic hadrons. Nucleus-nucleus collisions at the LHC offer a possibility to achieve this goal. The yield of T + cc 's produced at the end of the quark-gluon plasma phase of nuclear collisions is related to the internal structure of the state. However this yield may be affected by the interactions in the hadron … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
16
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(17 citation statements)
references
References 27 publications
1
16
0
Order By: Relevance
“…Its minimum valence quark content is ccū d. From the data, the binding energy with respect to the D * + D 0 mass threshold and the decay width are estimated to be 273 ± 61 ± 5 +11 −14 keV and 410 ± 165 ± 43 +18 −38 keV, respectively, which are consistent with the expected properties of a T + cc isoscalar tetraquark ground state with J P = 1 + [3][4][5][6][7][8][9][10][11][12][13][14]. Since its detection, many works appeared debating the possible mechanisms of its decay/formation and trying to answer the question of whether it is an extended hadron molecule or a compact tetraquark [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30].…”
Section: Introductionsupporting
confidence: 62%
See 4 more Smart Citations
“…Its minimum valence quark content is ccū d. From the data, the binding energy with respect to the D * + D 0 mass threshold and the decay width are estimated to be 273 ± 61 ± 5 +11 −14 keV and 410 ± 165 ± 43 +18 −38 keV, respectively, which are consistent with the expected properties of a T + cc isoscalar tetraquark ground state with J P = 1 + [3][4][5][6][7][8][9][10][11][12][13][14]. Since its detection, many works appeared debating the possible mechanisms of its decay/formation and trying to answer the question of whether it is an extended hadron molecule or a compact tetraquark [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30].…”
Section: Introductionsupporting
confidence: 62%
“…In this sense, in Ref. [28] we have suggested that a good environment to study the T + cc properties is the one provided by heavy ion collisions (HIC), where a large number of charm quarks is produced. In a typical HIC, there is a phase transition from nuclear matter to the locally thermalized state of deconfined quarks and gluons -the socalled quark-gluon plasma (QGP), which expands, cools down and becomes a gas of hadrons.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations